2017
DOI: 10.1074/jbc.m117.795617
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the extent of structural heterogeneity in α-synuclein fibrils by the small molecule thioflavin T

Abstract: The transition of intrinsically disordered, monomeric α-synuclein into β-sheet-rich oligomers and fibrils is associated with multiple neurodegenerative diseases. Fibrillar aggregates possessing distinct structures that differ in toxicity have been observed in different pathological phenotypes. Understanding the mechanism of the formation of various fibril polymorphs with differing cytotoxic effects is essential for determining how the aggregation reaction could be modulated to favor nontoxic fibrils over toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 91 publications
4
29
0
Order By: Relevance
“…Kim et al (2013) have shown, however, that αS oligomers spontaneously secreted by a neuroblastoma cell line had the potential to activate TLR-2 in microglial cells whereas fibrils produced from recombinant αS were unable to do so. Such discrepancies may be because of structural heterogeneity of αS oligomeric and fibrillary species in between studies (Bousset et al, 2013: Kumar, Singh, Kumari, & Udgaonkar, 2017. Glutamate release induced by αSa was also significantly curtailed by JNJ, a synthetic antagonist for purinergic P2X7 receptors (Letavic et al, 2013), which is reminiscent to previous studies showing that oligomeric forms of αS bind directly to this receptor subtype .…”
Section: αSa-mediated Glutamate Release In Microglial Cells Is Medimentioning
confidence: 52%
See 1 more Smart Citation
“…Kim et al (2013) have shown, however, that αS oligomers spontaneously secreted by a neuroblastoma cell line had the potential to activate TLR-2 in microglial cells whereas fibrils produced from recombinant αS were unable to do so. Such discrepancies may be because of structural heterogeneity of αS oligomeric and fibrillary species in between studies (Bousset et al, 2013: Kumar, Singh, Kumari, & Udgaonkar, 2017. Glutamate release induced by αSa was also significantly curtailed by JNJ, a synthetic antagonist for purinergic P2X7 receptors (Letavic et al, 2013), which is reminiscent to previous studies showing that oligomeric forms of αS bind directly to this receptor subtype .…”
Section: αSa-mediated Glutamate Release In Microglial Cells Is Medimentioning
confidence: 52%
“…Our result is in agreement with data reported by Gustot et al (2015) showing that αS amyloid fibrils can trigger inflammatorytype reactions through a TLR-2-dependent mechanism. Such discrepancies may be because of structural heterogeneity of αS oligomeric and fibrillary species in between studies (Bousset et al, 2013: Kumar, Singh, Kumari, & Udgaonkar, 2017. Such discrepancies may be because of structural heterogeneity of αS oligomeric and fibrillary species in between studies (Bousset et al, 2013: Kumar, Singh, Kumari, & Udgaonkar, 2017.…”
Section: αSa-mediated Glutamate Release In Microglial Cells Is Medimentioning
confidence: 99%
“…Now it is known that aSyn exists in oligomeric form during the lag phase of brillization process. 56,57,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74] So then a question arises that is the disappearance of peaks for stretches of residues in the free aSyn HSQC spectrum (Fig. 3A) due to the oligomerization of the protein?…”
Section: Resultsmentioning
confidence: 99%
“…One of the defining features of amyloids is polymorphism, and it has been shown that most of this polymorphism arises during the nucleation of the fibrillization reaction . Different forms of fibrils and/or soluble oligomers (precursors of fibrils) may have different degrees of neurotoxicity or interact differently with diagnostic or therapeutic reagents (e.g., antibodies) . For these reasons, the identification of biologically relevant heterogeneous nucleators is a point of potentially great importance.…”
Section: Fibrillization Of Aβ Peptides and Heterogeneous Nucleationmentioning
confidence: 99%
“…[27][28][29] Different forms of fibrils and/or soluble oligomers (precursors of fibrils) may have different degrees of neurotoxicity or interact differently with diagnostic or therapeutic reagents (e.g., antibodies). [30][31][32] For these reasons, the identification of biologically relevant heterogeneous nucleators is a point of potentially great importance.…”
Section: Fibrillization Of Aβ Peptides and Heterogeneous Nucleationmentioning
confidence: 99%